2000
DOI: 10.1006/jmsc.2000.0717
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of small tunas by a purse-seine fishery with fish aggregating devices and their feeding ecology in an eastern tropical Atlantic ecosystem

Abstract: We investigated the effects of a purse-seine fishery with drifting fish aggregating devices (FADs) in the South Sherbo area of the Equatorial Atlantic, located between 0-5"N and 10-2o"W. There had been no surface fishing activity in the area until 1975. Since 1991, fishing operations on schools of tuna associated with FADs has become widespread and this offshore area has developed into a major fishing zone. Exploitation rates are high between November and January. The fishery exploits multispecies concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 4 publications
0
34
1
1
Order By: Relevance
“…The Picolo area is known to support large concentrations of juvenile tunas likely due to oceanographic-specific conditions (Evans et al 1981;Prince et al 2010) and to the abundance of mesopelagic fishes, such as Vinciguerria nimbaria, which is one of the favorite preys of juvenile tunas in this region (Menard et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The Picolo area is known to support large concentrations of juvenile tunas likely due to oceanographic-specific conditions (Evans et al 1981;Prince et al 2010) and to the abundance of mesopelagic fishes, such as Vinciguerria nimbaria, which is one of the favorite preys of juvenile tunas in this region (Menard et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…at 5 kg or less (Menard et al 2000). Small tunas are seasonally important to artisanal and recreational fisheries in many areas around the Atlantic Ocean.…”
mentioning
confidence: 99%
“…Moreover, in the Gulf of Guinea there are complex process of reproduction, recruitment and behavioural interaction with the environment and fishing strategy that also could increase the variability of skipjack captures Pallares-Soubrier 1996, Solari et al 2003). Ménard et al (2000) suggested that the FAD fishery may have wide-ranging effects on the migration of tunas in general and on the productivity of the skipjack population in particular. The behaviour of the scatter plot of the relationship between reconstructed and observed data suggests that for a high percentage of missing data, over 40%, the fit became worse, probably because the central limit theorem is not satisfied.…”
Section: Discussionmentioning
confidence: 99%